2019
DOI: 10.1111/1365-2656.12971
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of elephant foraging behaviour in a coupled human‐natural system: Is brown the new green?

Abstract: Crop raiding by wildlife poses major threats to both wildlife conservation and human well‐being in agroecosystems worldwide. These threats are particularly acute in many parts of Africa, where crop raiders include globally threatened megafauna such as elephants, and where smallholder agriculture is a primary source of human livelihood. One framework for understanding herbivore feeding behaviour, the forage‐maturation hypothesis, predicts that herbivores should align their movements with intermediate forage bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 60 publications
2
55
0
1
Order By: Relevance
“…Similarly, knowledge of key stands of fruiting trees visited by elephants could orient seasonal anti-poaching patrols and efforts. Most elephant follows occurred within relatively pristine protected areas: future work should investigate drivers of elephant movement around settlements as forest elephants may alter their foraging behavior at humanwildlife interfaces (see Branco et al (2019) where this was demonstrated for savannah elephants). In the same way that responses to fruit availability and rainfall vary among individuals, elephants may also demonstrate individual behavior in their tendency to approach settlements and raid crops (Swan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, knowledge of key stands of fruiting trees visited by elephants could orient seasonal anti-poaching patrols and efforts. Most elephant follows occurred within relatively pristine protected areas: future work should investigate drivers of elephant movement around settlements as forest elephants may alter their foraging behavior at humanwildlife interfaces (see Branco et al (2019) where this was demonstrated for savannah elephants). In the same way that responses to fruit availability and rainfall vary among individuals, elephants may also demonstrate individual behavior in their tendency to approach settlements and raid crops (Swan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, EVI slope had the highest predictive power among all EVI variables, implying possible importance of vegetation phenology. A study of crop raiding behavior in African elephants identified crop availability and ripening timing as important indicators for predicting crop damage [82]. Therefore, variables related to crop types along with its phenology, which can be detected from remotely sensed satellite data, should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Elephants are now recovering under the auspices of the Gorongosa Project (Pringle, 2017), and the most recent aerial census counted roughly 600 individuals (Stalmans et al, 2019). After the war, however, much of the buffer zone has been converted to agricultural lands ( Figure S1, Appendix S1), which strongly attract elephants (Branco et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…(Male elephants are generally more prone to crop-raiding behavior: Hoare, 1999. ) A detailed description of our capture and handling procedures is provided by Branco et al (2018); all procedures were approved by the Animal Care and Use Committee at the University of Idaho (protocol #2015-39). In addition, our research was certified as exempt from continuing review by the Institutional Review Board at the University of Idaho.…”
Section: Animal Capture and Location Datamentioning
confidence: 99%